Y-shaped alkynylimidazoles as effective push-pull fluorescent dyes for luminescent solar concentrators (LSCs). (May 2022) - Rosadoni, Elisabetta; Bellina, Fabio; Lessi, Marco; Micheletti, Cosimo; Ventura, Francesco; Pucci, Andrea
Abstract: The synthesis of three 2-arylalkynyl-4, 5-diarylimidazoles endcapped with typical electron-donating (ED) and electron-withdrawing (EW) groups (push-pull system) and their evaluation as fluorescent dyes for thin-film luminescent solar concentrators (LSCs) is described. These novel Y-shaped imidazole-based fluorophores were easily assembled in good chemical yields through a three-step synthetic sequence involving a double Suzuki arylation, followed by a dehydrogenative alkynylation, and a Knoevenagel condensation. Their optical and spectroscopic properties were analyzed both in solution and in poly(methyl methacrylate) (PMMA) films. All the molecules in PMMA films showed an intense, red-shifted emission between 540 and 575 nm with large Stokes shift (>120 nm), moderate-to-good fluorescence quantum yields (QY) and good device efficiencies (ηdev ), especially for compound 3 . Highlights: New 2-arylalkynyl-4, 5-diarylimidazoles were obtained via a simple three-step synthetic pathway. Photophysical properties studied as a function of the different electron-withdrawing groups. Homogeneous PMMA films containing the fluorophores were realized with max QY of 0.6 Overall good LSC efficiencies were collected.